AB0726 Severe Obesity Is Frequent in Patients with Psoriatic Arthritis and Is Accompanied by Increased Cardiovascular Risk. (15th July 2016) - Huscher, D.; Albrecht, K.; Bischoff, S.; Thiele, K.; Behrens, F.; Hoese, G.; Ochs, W.; Zink, A.
Abstract : Background: It is known that patients with psoriatic arthritis (PsA) are at increased risk of obesity and associated cardiovascular comorbidity, in particular those with severe and long-standing disease (>10 years). There is less information on the frequency of obesity and cardiovascular risk in patients with incident or medium-term disease. Objectives: To investigate the prevalence of obesity compared to the population, disease presentation and the cardiovascular morbidity at onset of disease and after a mean of five years disease. Methods: We selected two discrete groups of patients with a PsA diagnosis (M07.0-M07.3) enrolled in the national database of the German Collaborative Arthritis Centres between 2003 and 2014: patients with either short (≤0.5 years) or longer disease duration (between 4 and 6 years). Stratified by BMI classes, disease activity and cardiovascular comorbidity, as well as the deviation of the BMI from the age- and sex-matched normal population were analysed. Results: 421 patients were enrolled with incident disease (mean disease duration 3.0 months) and 965 with medium-term PsA (mean 5.0 years). Both the BMI distribution in general and the portion of patients with severe obesity (BMI≥35, ∼8%) were similar in incident and medium-term PsA. In comparison to the age- and sex-matched population, obesity was more frequent in patients with incident (23.5% vs. 16.1%) as well as in medium-term PsA (24.7% vs. 17.4%). Obesity was associated with higher disease activity, higher patient-reported burden and substantially higher prevalence of cardiovascular risk factors already in early PsA except for significantly lower smoking rates (Table1 ). In medium-term PsA, 23.6% of all patients (mean age 52 years) and 36.1% of the obese patients (mean age 54 years) presented with any cardiovascular risk factor (diabetes, hypertension, hypercholesterolemia or heart disease); in obese patients the prevalence of coronary heart disease (10.1%) was doubled compared to incident patients. Table 1 shows patient characteristics in incident PsA. Conclusions: One quarter of the patients with PsA are obese, already at the onset of the disease, and they present with more severe obesity than the age and sex matched normal population. The high cardiovascular comorbidity at onset of PsA is further significantly increased in obese patients already after five years of disease. This should be considered in the treatment of these patients. Acknowledgement: The database was funded by the German Federal Minister of Research from 1999 to 2007 (grant #01 GI 0344/3). Since 2007, the Working group of the regional collaborative arthritis centres and a consortium of pharmaceutical companies has been funding the National Database by an unconditional grant to the German Society for Rheumatology. Disclosure of Interest: None declared